1985
DOI: 10.1002/ajmg.1320200211
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic and cytogenetic spectrum of partial trisomy 9

Abstract: A new patient with trisomy for the chromosome segment 9pter----q22 is compared to 19 previously reported cases of partial trisomy 9. Manifestations such as microcephaly, prominent nasal root, bulbous nose, and down-turned corners of the mouth are common to patients with trisomic segments extending from 9p21 to 9q13, while intra-uterine growth retardation, cleft lip/palate, skeletal anomalies, and heart defects are more common with trisomic segments extending through 9q22-9q32. A graphic method illustrates this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 19 publications
(1 reference statement)
3
53
0
Order By: Relevance
“…Distinct radiologic abnormalities of the hands, feet, and pelvic bones have also been described [Schinzel, 1979]. Wilson et al [1985] demonstrated that the spectrum of clinical severity in trisomy 9p correlates with the extent of the trisomic chromosome 9 material. Mental retardation is usually present.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Distinct radiologic abnormalities of the hands, feet, and pelvic bones have also been described [Schinzel, 1979]. Wilson et al [1985] demonstrated that the spectrum of clinical severity in trisomy 9p correlates with the extent of the trisomic chromosome 9 material. Mental retardation is usually present.…”
Section: Discussionmentioning
confidence: 95%
“…Partial or complete duplication of the short arm of chromosome 9 was reported in approximately 150 cases and has been reviewed previously [Centerwall and Beatty-Desana, 1975;Smart et al, 1988;Wilson et al, 1985;Young et al, 1982]. The trisomy 9p phenotype includes growth and developmental retardation, typical facial appearance and hand abnormalities, most frequently brachydactyly (Tables I and II).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, chromosome 9, which is orthologous to large parts of the chicken Z, is highly structurally polymorphic in humans (Humphray et al, 2004). Trisomies of human 9p (Wilson et al, 1985), and monosomies of 5q and 18q (which all share homology with the chicken Z), survive to birth (Nusbaum et al, 2005;Boultwood et al, 2010). Moreover, the snake Z chromosome is known to share homology with human 3p21-p24, 7p14-p15, 10p11-p15 and 17q21-q24 (Matsubara et al, 2006).…”
Section: Does Dosage Insensitivity Predispose An Autosome To Evolve Smentioning
confidence: 99%
“…The phenotype of this child is mild according to the partial trisomy 9p malformation spectrum described by Wilson et al [1985]. He had mild psychomotor delay and nearly normal growth, as usually described [Fryns et al, 1979].…”
Section: Discussionmentioning
confidence: 94%
“…After the original publication by Réthoré et al [1970], trisomy of the short arm of chromosome 9 became a clinically recognizable syndrome. Almost 150 patients with partial or complete 9p trisomy have been reported, but most patients had an unbalanced translocation involving another chromosome [Young et al, 1982;Wilson et al, 1985]. Ten published cases involved a de novo duplication [Chiyo et al, 1976;Baccichetti et al, 1979;Fryns et al, 1979;Zadeh et al, 1981;Cuoco et al, 1982;Motegi et al, 1985;Mattina et al, 1987;Bussani Mastellone et al, 1991;Phelan et al, 1993;Fujimoto et al, 1998], and one case was a direct inherited duplication [Haddad et al, 1996] (Table I).…”
Section: Discussionmentioning
confidence: 95%